Evaluación técnico-financiera del uso de diferentes combustibles en la generación eléctrica para la extensión del límite económico del campo Zopilote (2018)
The operability of a field is based on its lifting cost. Lifting cost is a term includes the costs incurred for the production of oil after the drilling of a well and before its treatment, commercialization and / or transportation. Without the operation, maintenance and administration costs, a field can close prematurely or slowly causing. The method par excellence to determine the useful life of a field is the calculation of its lifting cost based on the different costs of the field, the elaboration of the curve of declination of the production and the determination of an economic limit with a value of the barrel of oil.